(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
Firstly, the main ideas that support the teaching and learning of mathematics in the first ages are exposed from the perspective of Realistic Mathematics Education, and a review of the main contemporary curricular orientations in relation to the teaching of the measure in Early Childhood Education is presented. In the second part, two realistic learning experiences of the measure in Early Childhood Education are presented. The experiences, called "Chocolate bars" and "Chocolate cakes" respectively, have been carried out with 22 children from the 3rd year of Early Childhood Education (5-6 years) of the CEIP of Sigüeiro (La Coruña, Spain). The collected documentation shows how students discover in real or realistic situations various aspects related to measurement knowledge: they use quantifiers of length measurement, compare according to length, use length and mass measurement tools and progressively the Metric System Decimal.